Cemetery boys - Thomas, Aiden (Swoon Reads, 2020)
Yadriel, a trans boy, summons the angry spirit of his high school's bad boy, and agrees to help him learn how he died, thereby proving himself a brujo, not a bruja, to his conservative family.